The Role of Islam Nusantara and Nahdlatul Ulama on The National Challenges of Indonesia - Eli Oktaviani; Endang Suherman; Ahmad Pathony; Dusman Samsudin; Hapipi Hapipi; Muhamad Qustulani (International Research and Development for Human Beings (IRDH), 2024)
Islam is a faith that is believed to be revealed, with a guiding principle of 'Rahmatan li al-'alamin'. Islam Nusantara is not considered to be the standard form of Islam, but rather a unique and observable manifestation of Islam in Indonesia. This has been developed through interactions, adapting to the local context, translating and incorporating local elements, and making it accessible to the Indonesian society. The purpose of this study is to explore the significance of Islam Nusantara and Nahdlatul Ulama in addressing the challenges faced by Indonesia as a nation. The process of globalization poses a notable challenge to Nahdlatul Ulama, as it directly impacts the religious foundation of the people, namely Islam Nusantara (Aswaja), and the pillars of Indonesian nationality, particularly in terms of economic independence.